Faktor-Faktor Yang Mempengaruhi Under-reporting of Time - Ismawati Haribowo; Ismail Marzuki (Esensi: Jurnal Bisnis dan Manajemen, 2014)
This research examined the influenced of time pressure, audit risk, materiality, locus of control, and turnover intention to underreporting of time. Respondent in this research were the auditors who worked at Public Accounting Firm in DKI Jakarta. The respondences of this research were 120 auditors from 25 Public Accounting Firm. The sampling method in this research was purposive sampling method, while the data analysis method used multiple regression analysis. These result that time pressure, audit risk, and materiality had influence to underreporting of time. Locus of control and turnover intention had no influence to underreporting of time. Therefore, distribution of working time, condusive working environment, close supervision in field work, familial attachment auditor and auditor’s prosperity need to be done in order to avoid audit reporting practice prior to the specified reporting period or underreporting of time.DOI: 10.15408/ess.v4i3.2433